Managing salinity in the Indus Basin of Pakistan - Qureshi, Asad Sarwar; Sarwar, A. (2009)
Waterlogging and salinity have plagued irrigated agriculture in the Indus Basin for the past 30-40 years. Approximately 6 million ha (35-40% of total irrigated area) experience these twin problems. As a result, the production potential of the Indus Basin has been reduced by 25%. Over the last 40 years, the Government of Pakistan has adopted engineering, reclamation, and biological measures to address these problems. Part of the engineering solution involved large-scale Salinity Control and Reclamation Projects (SCARPs) in all four provinces. The program covered 8 million ha and cost approximately US$2 billion. Two big disposal projects were also initiated to solve the drainage disposal problems. To address the saline soil problem, some of the measures tested include leaching of salts by excess irrigation, use of chemicals (such as gypsum and acids), and addition of organic matter and biological measures (such as salt-tolerant plants, grasses, and shrubs). The success of these initiatives has been limited: 35-40% of irrigated land still suffers from high water tables and moderate to severe salinity. Lack of coordination among federal and provincial governments, research institutes, and national and international organizations; conventional farming and irrigation methods used by farmers; limited attention to reclamation and saline agricultural approaches; and lack of resources are some of the reasons for the low success rate. A more concerted effort that includes a greater focus on saline agriculture, capacity building of farmers, and promotion of local interventions to improve self-reliance is necessary for the management of salinity in the Indus Basin. A sustainable solution would also require coordination among different provinces and strengthening of federal and provincial government agencies.